Development of DNA Barcode for Magnoliopsida and Liliopsida using In silico Approaches Based on mat-K Sequences from Chloroplast Genomes - Denia Dwi Citra Resmi; Topik Hidayat; Siti Sriyati (Jurnal Biodjati, 2021)
Indonesia has been estimated to contain 20,000 species of Magnoliophyta around the world. The current status of Indonesia's biodiversity shows that only 15.5% of the total flora in Indonesia has been identified. This is such a low percentage, requires researchers to obtain a rapid identification method, so that unidentified species can be grouped, at least at the level of the Magnoliopsida and Liliopsida classes. DNA barcoding is a technique that can be used to quickly identify species based on short sequences of specific regions in the genome. The purpose of this study was to analyze the relationship between Magnoliopsida and Liliopsida plants based on the mat-K marker and to obtain DNA barcodes for each of the Magnoliopsida and Liliopsida classes. This study used an in silico approach because the molecular data about these two selected classes with 101 species for samples are abundant in Genbank NCBI database. The primary design was carried out after analyzing the phylogenetic relationship between Magnoliopsida and Liliopsida. In silico analysis using BioEdit and PAUP to reconstructthe phylogenetic tree based on mat-K DNA showed results that were in line with previous studies. The phylogenetic tree using molecular data confirms that Magnoliopsida is the ancestor of Liliopsida. This study succeeded in obtaining two pairs of specific primers for Magnoliopsida and Liliopsida, which are cttcagtggtacggagtcaaat and gagccaaagttttagcacaagaa for Magnoliopsida, whereas cccatccatatggaaatcttggt and ttgaagccagaattgcttttcc for Liliopsida. These primers can later be used to distinguish the Magnoliopsida group from Liliopsida.